2022
DOI: 10.1111/jcpp.13697
|View full text |Cite
|
Sign up to set email alerts
|

Research review: Effects of parenting programs for children's conduct problems on children's emotional problems – a network meta‐analysis

Abstract: Background Specific programs are often implemented for specific child mental health problems, while many children suffer from comorbid problems. Ideally, programs reduce a wider range of mental health problems. The present study tested whether parenting programs for children's conduct problems, and which individual and clusters of program elements, have additional effects on children's emotional problems. Methods We updated the search of a previous systematic review in 11 databases (e.g., PsycINFO and MEDLINE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Generally, parenting programs help enhance parent-child relationships. Hence, they help in alleviating emotional problems among children and strengthening family bonding [18]. This study found that the SMART parenting program was highly effective in promoting parenting behavior and minimizing t he risk of behavioral problems among school children.…”
Section: Discussionmentioning
confidence: 80%
“…Generally, parenting programs help enhance parent-child relationships. Hence, they help in alleviating emotional problems among children and strengthening family bonding [18]. This study found that the SMART parenting program was highly effective in promoting parenting behavior and minimizing t he risk of behavioral problems among school children.…”
Section: Discussionmentioning
confidence: 80%
“…In the future, intervention studies focusing on improving parent-child interaction and parenting practices could be a way to investigate effective ways to reduce inequalities in childhood mental health. Some randomized controlled trials on the topic already exist, and a review of evidence shows that they have been effective, but the positive impact fades away over time ( Kjøbli et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral-management interventions are wellestablished as effective in reducing externalizing probems (32), but research also suggest potential for reducing child internalizing behaviors (33). However, there is indication that the externalizing parent training programs need to be optimized to better t the internalizing symptom domains (34). In sum, these three types of family focused interventions have been found effective in reducing externalizing problems, although through somewhat different pathways.…”
Section: Background For the Sparck Contentmentioning
confidence: 99%